The Relationship between the Sports Manager Behavior and Locus of Control of Students Taking Sports Management Education - Kepoglu, Abdurrahman (Asian Journal of Education and Training, 2021)
The study aims to determine the degree to which sports managers show behaviors related to management processes and to what extent the focus of control of sports managers affects these behaviors, to increase the performance of sports managers. The universe of the research consists of 1st, 2nd, 3rd, and 4th-year students studying at the Department of Sports Management of Uşak University. The sample of the study, which was conducted with the non-probabilistic sampling method, in which 95% confidence level and 5% margin of error were used, consisted of 231 students, male = 155, female = 76. “Sports Manager Behavior Scale” and “Internal-External Locus of Control Scale” were used in the study. In general, it was determined that the students participating in the research have a very high level of sports manager behavior and internal-External Locus of Control. 95.7% of the students have internal control and 4.3% have an external locus of control.